Predictive toxicology for regulatory decisions: Implementing new approaches at US Food and Drug Administration. (March 2020) - Fitzpatrick, Suzanne C.
Highlights: FDA needs for Predictive Toxicology. FDA Predictive Toxicology Roadmap. Qualification of New In Vitro Methods. Importance of Working with Stakeholders in Advancing New Methods.